Are Labor Force Participation Rates Really Non-Stationary? Evidence from Three OECD Countries - Zeynel Abidin Ozdemir; Mehmet Balcilar; Aysit Tansel (Koç University-TÜSİAD Economic Research Forum (ERF), 2012)
This paper shows that the structural breaks are an important characteristic of the monthly labor force participation rate (LFPR) series of Australia, Canada and the USA. Therefore we allow for endogenously determined multiple structural breaks in the empirical specifications of fractionally integrated ARMA model. The findings indicate that contrary to the previous research the LFPRs of Australia, Canada and the USA are stationary implying that the informational value of the unemployment rates about the behavior of labor markets and the causes of joblessness are useful.
Keywords: C22; E24; J21; 330; Labor Force Participation Rates; Structural Change; Stationarity; Erwerbstätigkeit; Strukturbruch; Stochastischer Prozess; Schätzung; Kanada; USA; Australien